The zika virus disease: An overview - Galán Huerta, Kame Alberto; Rivas Estilla, Ana María; Martinez Landeros, E. A.; Arellanos Soto, Daniel; Ramos Jiménez, Javier (UANL. Facultad de Medicina, 2016)
The zika virus, another re-emerging Flavivirus transmitted to humans by mosquitoes, is responsible for the most recent fever outbreak in the Americas and the Pacific, starting in 2015. The immunologically naïve population in the Americas favors the spread of epidemics. The zika fever is characterized by febrile illness, malaise, conjunctivitis and a maculopapular rash. Similar to other arboviroses recently spread in the Americas, there is no specific or effective antiviral therapy and vaccines are still in trials. The only effective preventive measures consist of individual protection against mosquito bites and vector control. This febrile illness increases the epidemiological and public health challenge existing in America, where the population is already fighting against dengue and chikungunya fever. Disease prevention is important due to the economic burden it entails. The fact of sexual and transfusion virus transmission is a great challenge to overcome. Doctors need to distinguish between dengue, chikungunya and other diseases to give a successful treatment and prevent the disease spreading.